TRENDS IN THE DEVELOPMENT OF THE INDUSTRIAL SECTOR DURING THE DEEPENING OF STRUCTURAL CHANGES IN UZBEKISTAN - Salimjonova Zilola (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the difficult conditions of the transition to a market economy in Uzbekistan, the policy is based on a coherent and well-thought-out structural and industrial policy combined with liberalization of access to the world market and protectionist measures.